Alien amphipods (Arthopoda; Crustacea) in the Tista Estuary, Halden, southeastern Norway - Ingvar Spikkeland (Norwegian University of Science and Technology, 2021)
Two new amphipods for Norway Melita nitida and Corophium multisetosum (Crustacea; Amphipoda) were registered in brackish waters in the Tista Estuary in Halden, southeastern Norway. Both species were found in the samples from Tista’s outlet into the Idde Fjord, C. multisetosum in the beach zone and M. nitida at about 4 m depth. Melita nitida is a North American species first found in Europe in the Netherlands in 1998, and since then dispersed into the Baltic Sea via the Kiel Canal and now also found several places on the German Baltic Sea coast and in the Black Sea. Corophium multisetosum was collected even before the 1920s in Western Europe, and is considered native for Europe, whereas its relationship to North America is more ambiguous. From the British Isles and the Netherlands, it seems to have spread to Germany, Poland, Denmark and Sweden, and at present Norway. Until now the two species were found in small numbers at the Norwegian sites and their influence on the total benthic community is probably negligible in this initial phase. The Tista Estuary in Halden apparently appears to be a hotspot for alien brackish water species in Norway. Generally estuaries, with their combination of brackish water jointly with their unsaturated ecological niches and intensive international ship traffic, seem to possess the highest potential infection rate for aquatic systems with alien acrozoobenthic species.